Synthesis of Zeolite-A Pellets from Bangka Kaolin and Its Application in Ethanol Dehydration - Ulfah, Maria; Pasymi; Amir, Amelia; Iqbal, M; Hadi, Nandita (Universitas Nusa Bangsa, 2025)
Indonesia has abundant natural clay resources, including kaolin. In the Bangka Belitung Province, the kaolin reserves are estimated at 376,687,532 tons with identified reserve reaching 5,990,630 tons. The primary mineral constituents of kaolin are alumina and silica, which are essential raw materials for zeolite synthesis. Additionally, kaolin is widely utilized as a binder in various industrial applications. The research aimed to evaluated the potential of kaolin as a source of alumina and silica, as well as its effectiveness as a binder. This study investigated the influenced of calcination temperature and the composition of reactants (metakaolin, NaOH, and water) on the the performance of zeolite A pellets. The general process for yielding zeolite A pellets involved three main stages: transforming kaolin to metakaolin; preparing zeolite A powder and forming the pellets by mixing the synthesized zeolite A powder with calcined kaolin (metakaolin). In this study, kaolin was calcined at two temperatures at 570°C and 670°C, to produce metakaolin. The variables adjusted in the production of zeolite. The molar ratios of H2O to Na2O used in zeolite synthesis were varied at 37, 40, and 43, while the molar ratio of SiO2 to Al2O3 was maintained at 2.4, based on the chemical composition of the kaolin. Additionally, the Na2O to SiO2 ratio was kept constant at 2.5. X-ray diffraction (XRD) analysis confirmed that the synthesized material was zeolite A. The performance of the developed zeolite A pellets was found to be comparable to that of commercial catalysts. The optimal synthesis conditions were achieved with an H2O/Na2O ratio of 43 and kaolin calcined at 670°C. These results demonstrate that Bangka kaolin serves considerable potential for use both as a source of alumina and silica, and as a binder.